2002
DOI: 10.1002/app.10337
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis in inverse emulsion and properties of water‐soluble associating polymers

Abstract: An inverse, free-radical emulsion polymerization technique was designed for the preparation of copolymers of acrylamide and sodium acrylate modified with low amounts (Ͻ0.5 mol %) of a series of amphiphilic comonomers, the isooctylphenoxypoly(oxyethylene)(n) methacrylates (1 Յ n Յ 12). The products of the reaction were hydrophobically modified water-soluble polymers (HMWSPs) of high molecular weight encapsulated within water droplets dispersed in an organic medium. Kinetic studies showed that the full-conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…The polymerizations were carried out at 18 ± 1°C except for diPh‐2–CUM‐O, for which a higher temperature (45°C) is required to solubilize the hydrophobic comonomer in the oil phase. The details of the experimental procedure of the polymerization were presented in a previous study 21. Recall that the final latex was diluted twofold with hexane and poured into an excess of methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerizations were carried out at 18 ± 1°C except for diPh‐2–CUM‐O, for which a higher temperature (45°C) is required to solubilize the hydrophobic comonomer in the oil phase. The details of the experimental procedure of the polymerization were presented in a previous study 21. Recall that the final latex was diluted twofold with hexane and poured into an excess of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the experimental procedure of the polymerization were presented in a previous study. 21 Recall that the final latex was diluted twofold with hexane and poured into an excess of methanol. The precipitated polymer was recovered by centrifugation and then repeatedly washed under stirring with the following solvents: methanol, isopropanol, and acetone.…”
Section: Polymerizationmentioning
confidence: 99%
“…Pabon et al [79] showed that the use of an inverse (mini)emulsion polymerization route allows one to increase considerably the solid contents in the final products (up to 25 wt %). The associative copolymers were formed of an acrylamide/sodium acrylate backbone hydrophobically modified with small amounts (~ 0.5 mol %) of a series of amphiphilic comonomers, isooctylphenoxy-poly(oxyethylene)(n) methacrylates (with 1 < n < 12.5).…”
Section: Amphiphilic and Associating Copolymersmentioning
confidence: 99%
“…Pabon et al have extended the inverse miniemulsion polymerization technique to the synthesis of hydrophobically modified water-soluble polymers (HMWSPs) [79]. The hydrophilic backbone of the copolymers was formed from an acrylamide/sodium acrylate (AAm/NaA) mixture.…”
Section: Amphiphilic and Associating Copolymersmentioning
confidence: 99%
“…The production of acrylic polymers by inverse emulsion polymerization has several advantages such as easy handling and fast water redispersion for specific uses such as thickening agents. 8,9 In addition, the inverse emulsion polymerization technique results in high molecular weight polymers that overcome the problems associated with the high viscosity levels reached during bulk, solution or dispersion polymerization approaches. 10 However, if the amount of active material in the final product is not sufficiently high, various drawbacks, such as the expensive transportation costs, may limit their market.…”
Section: Introductionmentioning
confidence: 99%